Interpreting the Sego Wiwit Religious Tradition and Its Potential as Teaching Materials for Foreign Speakers - Dian Uswatun Hasanah; Ali Imron Al-Ma’ruf; Angger Gilang Praditama; Sigit Arif Bowo; Iqbal Syahrul Akbar Al Aziz; Yusnami Quqotus Namia (Penamas, 2026)
Sego wiwit, as an agrarian tradition of Javanese society, has so far been studied merely as a cultural description, despite its great potential as teaching material for international students. International students require contextual material rooted in local culture to explore the transformation of cultural meanings, particularly within the sego wiwit tradition. This study aims to examine the history, ritual processions, symbols and philosophy of sego wiwit, as well as its relevance to the socio-cultural life of the community and to the education of international students. Research data, collected using a qualitative descriptive approach with ethnohistorical methods, was obtained through observation, in-depth interviews and documentation, and analysed using an interactive model. The research findings indicate that ‘sego wiwit’ functions as a medium of symbolic communication representing the harmonious relationship between humans, nature, and the community’s spirituality. Cultural and religious negotiation through the reinterpretation of ritual meaning—as an expression of gratitude and social solidarity—serves not only as a cultural heritage but also holds potential as learning material for international students based on local culture and for strengthening intercultural literacy.